PELATIHAN PENGEMBANGAN PRAKTIKUM IPA BERBASIS LINGKUNGAN - Salirawati, Das; Subiantoro, Agung Wijaya; Pujianto, Pujianto (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2011)
The objectives of this activity are improving knowledge about how to initiate environment  based  science  laboratory work  and  giving  more  infor- mation to make science teachers feel enthusiastic, interested, and commited to create,  develop  and  implement  science  laboratory  work  in  their  school creatively. The target of this activity is science teacher at Kodya Yogyakarta. As for  execution  methods  worn  in  this  activity  are  experiment,  discourse, discussion  of  information  and  presentation.  The  materials  are  conducting science laboratory work through environment based, some difficulties and the solution which are found in the science class while conducting laboratory work. Science laboratory work focuses on giving information to the student about how to optimize daily activities for science laboratory work. Training is conducted in a day at Junior High School 1 of Yogyakarta. Then, in another day (one week after training process), each science teacher have to demonstrate and present their laboratory work design. Generally, this activity has been succeeded in understanding and devaloping some skills of conducting environment  based science laboratory work. Through this activity, knowledges and experiences of creating and conducting of environment based science laboratory work has been understood by science teachers in Kodya Yogyakarta which are formed in MGMP forum. All participants are active and giving positive responses. Moreover, this activity has been succeeded in developing a design of science laboratory work. About 20 design have been created by all participants